First Step to Equity and Organization in Waiting Lines for Stone Surgery. Translation of Prioritization Scores - Guilherme Gentile; Fabio Carvalho Vicentini; Erik Montagna; Daniel Pérez-Fentes; Guilherme Pimenta Roncete; Artur Henrique Brito; Fabio Miranda Torricelli; Alexandre Danilovic; Carlos Alfredo Batagello; Eduardo Mazzucchi; William Carlos Nahas (International Brazilian Journal of Urology)
ABSTRACT Purpose: The use of patient prioritization tools is one of several methods to enhance the management of waiting times for elective surgeries. Developing these tools specifically for urinary stones in the Brazilian context may enhance queue management and increase patient satisfaction. This study aims to adapt two previously published scores, the WCWL (Western Canada Waiting List - general criteria) and the SCQ-score (specific to urinary stone criteria), into Brazilian Portuguese. Materials and Methods: Our study adhered to established protocols for the cross-cultural adaptation and translation of health-related questionnaires. The process for translating both original scores involved four steps: initial translation, back-translation, committee review, and pre-testing. The translations were conducted by professionals proficient in the relevant languages. The pre-test phase engaged eight endourologists who applied the translated versions of the scores to twelve hypothetical patient cases. Results: Our study successfully produced Brazilian Portuguese versions of the SCQ and WCWL scores. During the pre-testing, these scores were found to be quick to perform (with an average completion time of 1 minute and 35 seconds) and were deemed easy to understand and use by the endourologists. However, there was a concern regarding the practical utility and interpretability of the WCWL score due to its more generalized criteria. Conclusion: We successfully developed the Brazilian Portuguese version of the Western Canada Waiting List and SCQ-score. This development will allow further studies to evaluate the impact of their use within the Brazilian healthcare environment.